Farmer Awareness to the Dangers of Heavy Metal Cadmium (Cd) Pollution due to Over-Fertilization in Sragen Regency Central Java - Visnu Pradika; Mohammad Masykuri; Supriyadi Supriyadi (Universitas Sebelas Maret, 2019)
P fertilization can add Cd metal content to agricultural land because the raw material for making P fertilizer comes from phosphate rock which naturally contains Cd metal. Farmers assume that by providing fertilizers with high doses can provide maximum results. Community’s knowledge of heavy metals in the environment is still low. This study aims to examine the awareness of farmers in Sragen Regency Central Java to the potential of heavy metal pollution that occurs. This research was conducted from July to December 2017. The type of this research is quantitative descriptive research using a questionnaire with the number of respondents amounting to 10% of the number of farmers, namely 30 farmers. The results show that about 61.11% of the community doesn’t understand that the presence of heavy metals in the environment can cause many problems. About 60% of the community doesn’t understand that the inorganic fertilizers commonly used by them contain heavy metals (especially Cd metal). People unaware of heavy metal pollution due to over-fertilization is 65.01%. Although the community's knowledge and awareness of heavy metals are still low, the community awareness about environmentally friendly agriculture is high (61.33%). About 53.34% of the community doesn’t know that their behavior in using inorganic fertilizers in the long term will increase the accumulation of Cd metal in agricultural land and rice plant tissue. About 70% of the community doesn’t know that agricultural land that is used continuously to plant (without interspersed with non-paddy crops) will cause land degradation.